2015
DOI: 10.5812/atr.25313
|View full text |Cite
|
Sign up to set email alerts
|

Operative Treatment of Isolated Bicondylar Hoffa Fracture With a Modified Swashbuckler Approach

Abstract: Introduction:An isolated coronal fracture of either or both femoral condyles is a rare entity and is usually associated with high-energy injury trauma. Such fractures should be meticulously fixed for a good functional outcome as they involve the articular surface of a weight bearing joint. A modified swashbuckler approach provides adequate exposure for appropriate reduction and fixation of such fractures.Case Presentation:A 32-year-old male sustained a bicondylar Hoffa fracture of the right femur which was tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Therefore, we propose that a screw inserted in posterior to anterior direction would be appropriate. For this either swashbuckler approach [19, 20]/Gerdy’s tubercle osteotomy for lateral condyle [21] and subvastus approach for medial condyle would provide a better exposure [9]. We found that anterior to posterior lag screw was the most common method used for treating Hoffa’s fracture in the literature even when the fragment is small, even though postero-anterior screws have shown to have more biomechanical stability [22] (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we propose that a screw inserted in posterior to anterior direction would be appropriate. For this either swashbuckler approach [19, 20]/Gerdy’s tubercle osteotomy for lateral condyle [21] and subvastus approach for medial condyle would provide a better exposure [9]. We found that anterior to posterior lag screw was the most common method used for treating Hoffa’s fracture in the literature even when the fragment is small, even though postero-anterior screws have shown to have more biomechanical stability [22] (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…“ Type 4d ” is a Hoffa’s fracture with associated supracondylar fractures of the distal femur. This association has been seen in up to 38% cases, which can alter the management plan for distal femur fractures [20]. Use of longer, more rigid fixation with a locking buttress plate construct augmented by lag screws has been recommended [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When high-energy trauma involves the distal femur, the lateral condyle is often damaged [18] before the medial condyle because of the physiologic genu valgum of the knee joint. [19] Therefore, lateral condyle fracture is significantly more common than medial condyle fracture. [15,17–20] The fracture line its inclination angle of a Hoffa fracture depend on the degree of knee joint flexion at the time of trauma [18] ; as the angle of knee flexion increases, the fracture line will occur farther from the posterior cortex of the femoral-condyle.…”
Section: Injury Mechanismmentioning
confidence: 99%
“…When examining patients involved in a motor vehicle accident, regardless of vehicle type, additional imaging modalities should be acquired to rule out a Hoffa fracture. Depending on the severity of the trauma, fractures of the tibial plateau, distal femoral shaft, bicondylar femur, and patella are cited as factors that complicate the treatment and rehabilitation of Hoffa fractures [12][13][14][15][16] . Both isolated and non-isolated Hoffa fractures are associated with a higher intensity of trauma, leading to worsened patient presentations.…”
Section: Mechanism Of Injurymentioning
confidence: 99%